Adubação de sistemas e comportamento dos nutrientes em sistema de integração lavoura-pecuária - Huf, Flávia Levinski (2018)
The present work was conducted in an agricultural property located in the municipality of Abelardo Luz - SC, in the agricultural year of 2015/2016, consisting of the succession of three crops in the long - term ILP system, titling them in phases, Phase I = pasture , Phase II = silage maize and Phase III = bean second harvest. Thus, the objective of this work was to evaluate the effect of the interaction between the application of nitrogen fertilization in the different stages of cultivation of the ILP system with different grazing pressures on the nitrogen, phosphorus and potassium behavior in the soil, the nutritional status of corn silage and the bean crop, and evaluate the productivity of these crops in a crop-livestock integration system. The experimental design was a randomized block design with three replications, distributed in a factorial scheme (2x2), the first factor was N: N fertilization time applied to pasture (N-Pasture fertilization) and N applied to grain crops (N-Grain Fertilization) at a dose of 200 kg of N ha-1. The second factor was the Grass Height, characterized by two pasture management heights (High Height and Low Height). The use of systems fertilization practice did not cause loss of N-NO3 - leaching in the soil profile, even when performed in a single application of 200 kg of N ha-1. The low grass height intensifies nutrient cycling by potentiating the nitrogen fertilization practices, due to changes in soil biota and the quality of the residue remaining on the soil (straw). Nitrogen fertilization in ryegrass cover provided higher levels of available P in the soil after N application. Grazing and nitrogen fertilization on ryegrass cover stimulate plant growth and regrowth, causing K uptake by plants, reducing the possibility of losses. In the cultivation of maize for silage in ILP it is possible to reach adequate levels of nitrogen nutrition with the application of nitrogen in winter pasture cover, as well as in the crop itself in the summer. The dilution curve proposed by Lemaire e Salette (1984) for C3 plant species was not adequate for the diagnosis of nitrogen nutritional status for bean culture. The use of nitrogen fertilization in pasture cover and the management of less grazing intensities provides greater production of total ryegrass forage. The highest yields of common bean were obtained with the application of 100 kg ha-1 of N in coverage in the V4 stage.